Electrical stimulation in lower motoneuron lesions, from scientific evidence to clinical practice: a successful transition - Ines Bersch; Winfried Mayr (European Journal of Translational Myology, 2023)
Long pulse stimulation in its application in everyday clinical practice still represents a challenge for many therapists and clinicians. It is often unclear how the intervention setup, in particular the parameters pulse width, frequency and amplitude, can influence muscle morphology. In addition, the cause of damage to the lower motoneuron can have multiple reasons and is not anatomically located at the same site. Given the large heterogeneity, it is essential to know the current options and limitations in order to carry out a targeted treatment. A retrospective data analysis of n=128 patients, seen at the Swiss Paraplegic Centre (SPC) in 2022, shows a broad variability in manifestation of lower motoneuron damage. Treatment examples based on different causes of lower motoneuron damage are shown and corresponding stimulation programmes are assigned, as well as the expected results in terms of stimulation duration, volume and configuration.